Amoebic Gill Disease in the marine environment - Barbara Nowak; Carson, J; Powell, MD; Dykova, I (2002)
Amoebic Gill Disease (AGD) can cause considerable losses in aquaculture either due to mortalities or treatment costs. As it is the main health problem affecting sea-cage culture of Atlantic salmon in Australia, the recently funded Cooperative Research Centre for Sustainable Aquaculture of Finfish (Aquafin CRC) will include a comprehensive research programme focussed on AGD. The main objective of the roundtable discussion was to highlight the similarities and differences in AGD outbreaks around the world (related to geographic location and species-specificity of host and pathogen) and discuss control and treatment options for the disease and potential for international collaboration.